Automatic front-crawl temporal phase detection using adaptive filtering of inertial signals - Dadashi, F.; Crettenand, F.; Millet, G. P.; Seifert, L.; Komar, J.; Aminian, K. (Journal of Sports Sciences, 2013)
This study introduces a novel approach for automatic temporal phase detection and inter-arm coordination estimation in front-crawl swimming using inertial measurement units (IMUs). We examined the validity of our method by comparison against a video-based system.